Evaluasi Pelaksanaan E-Government di Kota Semarang - Zulfiyyan Effendy; Ari Subowo (Journal of Public Policy and Management Review, 2019)
E-Government is a new interaction mechanism between the government and public or private sector by involving the use of information technology with the aim of improving the quality of public services. Based on previous research shows that the city of Semarang has not reached the fourth level in the implementation of egovernment as stated in Presidential Instruction No. 3 of 2003. The purpose of this study was to determine and analyze the implementation and development of egovernment in the Semarang City Government so far and the factors influencing it. The method used in this research is qualitative descriptive. The results showed that the implementation of e-government in the city of Semarang in general has gone well. However, from the four levels of e-government implementation contained in Presidential Instruction No. 3 of 2003, the implementation of e-government in the city of Semarang has not yet reached the fourth level in overall because Semarang City doesn’t have an application that emphasizes the integration of G2G, G2B, and G2C services. The factors that influence the implementation of e-government in Semarang City are, lack of regulations for implementating e-government, lack of human resources, budget constraints financed by APBD, lack of attention from other OPD. To overcome the problems, government of Semarang city formulate regulations on the implementation of e-government so that Semarang City has a reference in the implementation, providing outsourcing personnel, making budget priority, and conducting socialization and routine supervision to other OPD.